Retrotransposon life cycle and its impacts on cellular responses - Ahmad Luqman-Fatah; Kei Nishimori; Shota Amano; Yukiko Fumoto; Tomoichiro Miyoshi (RNA Biology)
Approximately 45% of the human genome is comprised of transposable elements (TEs), also known as mobile genetic elements. However, their biological function remains largely unknown. Among them, retrotransposons are particularly abundant, and some of the copies are still capable of mobilization within the genome through RNA intermediates. This review focuses on the life cycle of human retrotransposons and summarizes their regulatory mechanisms and impacts on cellular processes. Retrotransposons are generally epigenetically silenced in somatic cells, but are transcriptionally reactivated under certain conditions, such as tumorigenesis, development, stress, and ageing, potentially leading to genetic instability. We explored the dual nature of retrotransposons as genomic parasites and regulatory elements, focusing on their roles in genetic diversity and innate immunity. Furthermore, we discuss how host factors regulate retrotransposon RNA and cDNA intermediates through their binding, modification, and degradation. The interplay between retrotransposons and the host machinery provides insight into the complex regulation of retrotransposons and the potential for retrotransposon dysregulation to cause aberrant responses leading to inflammation and autoimmune diseases.